Complete atrioventricular block in an adolescent with acute rheumatic fever: a case report - Sunbanu, Samlek Elisawyn (Indonesian Pediatric Society, 2024)
Acute rheumatic fever (ARF) is an autoimmune, multiorgan inflammatory disease that occurs in genetically susceptible individuals after group A-hemolytic streptococcal infection. Carditis and polyarthritis are the most common symptoms of ARF. Repeated streptococcal infections can cause recurrent valvulitis and valvular heart disease. Prolonged atrioventricular conduction (first-degree heart block) is a well-known symptom of ARF, occurring in one-fifth to three-fifths of patients. This condition is a minor criterion for diagnosing ARF based on Jones's criteria. Advanced conduction delay, such as a second-degree or a complete atrioventricular (AV) block, is a rare condition of ARF that can occur before symptoms like carditis, polyarthritis, and Sydenham chorea appear. We present a case of ARF in an adolescent with complete AV block.